Improved scaling laws for infrastructure: planning increased access to water and sanitation networks in low- and middle-income countries - Fernando Assad; Gabrielle Marega; Nitish Ranjan Sarker; David D J Meyer (Royal Society Open Science)
Despite efforts to expand infrastructure, billions of people still lack access to essential services. Traditional scaling-law (power-law) models of infrastructure estimate the size of infrastructure based on a city’s population, obscuring the consequences of inadequate access. Instead, we model infrastructure size as a power-law function of the population served by the infrastructure (not total population). This generalization better fitted data describing 6898 water and sewer networks in 53 countries—improving [Formula: see text] by up to 32%. Even in cities with little access to infrastructure, we found economies of scale: infrastructure that serves more people can do so with less per beneficiary. Uniquely, our generalized scaling laws can model the infrastructure needed to expand access. We validate with 16 years of data from 3391 water and sewer networks in Brazil. If economies of scale are exploited at the cost of inter-city equality, sewer access can expand from 54% to 90% of Brazil’s population with 29% (89 000 km) fewer new sewers. Benefit- and equality-maximizing strategies to achieve universal access in Brazil differ by 220 million people-years of access. Our generalized model can estimate the infrastructure needed to expand access and quantify trade-offs between the benefits and equality of access expansions.